Protamine sulphate coated poly (lactide-co-glycolide) nanoparticles of MUC-1 peptide improved cellular uptake and cytokine release in mouse antigen presenting cells. (16th November 2020) - Jyoti, Kiran; Katare, Om Prakash; Kamboj, Anjoo; Madan, Jitender
Abstract: Aim: MUC-1-peptide (M-1-pep) loaded poly (lactide-co-glycolide) nanoparticles were coated with protamine sulphate (PS), M-1-pep-PS-P-NPs for targeting antigen presenting cells (APCs) to evoke cytokine release. Methods and results: M-1-pep-PS-P-NPs were tailored by emulsion-diffusion evaporation method and characterised in vitro under a set of rigorous parameters. The average particle size and zeta potential of optimised M-1-pep-PS-P-B-NPs was measured to be 132.21 ± 30.71 nm and 6.29 ± 0.71 mV, significantly ( p < 0.01) higher than 71.24 ± 17.76-nm and −43.41 ± 3.37 mV of M-1-pep-P-NPs. Further, 50-μg/ml concentration of M-1-pep-PS-P-B-NPs displayed 82.4% cellular uptake in RAW 264.7 cells calculated in setting of fluorescence intensity significantly ( p < 0.05) elevated than 63.1% of M-1-pep-P-NPs. Consistent to quantitative results, M-1-pep-PS-P-B-NPs also confirmed advanced cellular uptake (CU) in RAW 264.7 cells in contrast to M-1-pep-P-NPs suppose to be through multiple mechanisms including phagocytosis and clathrin mediated endocytosis. Conclusion: M-1-pep-PS-P-B-NPs must be evaluated in vivo through inhalation route of administration for antitumor prospective in lung cancer xenograft model.